Poverty and the transformation of the welfare (state) arrangement. Food banks and the charity economy in Germany - Holger Schoneville (Social Work and Society)
We are currently witnessing a shift in the public response to poverty within our societies. The establishment and consolidation of food banks in Germany and in many other western European countries change the character of the welfare state. Food banks along with similar voluntary and charity-based institutions provide support in the form of basic goods (food, clothes, "¦), that have been collected as donations, to people in need. They are part of a sector, that has formed itself as a"charity economye". Behind the"charity economye" phenomenon lies a shift regarding the responsibility from the state towards private, voluntary actors. Within this shift not only the form - in which support is provided - changes from an approach that is based on individual rights towards an act of charitable"givinge", but also the target of the support itself: it is focused on alleviating poverty but is neither intended nor capable of fighting the structural conditions which constitute poverty. These transformations in the way in which modern Western societies respond to poverty constitute a different form of relationship between individuals, the state and society as a whole; they are a part and a symbol of the rearrangement of the social.